COMPARATIVE ANTIFUNGAL ACTIVITY of FLAVONOID EXTRACTS FROM Senna siamea AND Cnidoscolus chayamansa AGAINST BANANA CROWN FUNGI - Chotpong, Chutikarn; Chamnikla, Dunyaphat; Wareekhun, Nanticha; Donsopon, Sakonlanun; Phoolaenkee, Atcharawadee; Janhom, Nitchanan; Bunnaen, Wutthisak Wut; Bunban, Daungdeun (Jurnal Pendidikan Matematika dan IPA, 2026)
This study compared the antifungal efficacy of flavonoid extracts from Senna siamea and Cnidoscolus chayamansa against fungi isolated from banana crown using Potato Dextrose Agar (PDA) medium. Leaf extracts were prepared using ethanol maceration (1:10 w/v) for 24–48 h under dark conditions. Antifungal activity was evaluated by measuring radial fungal growth for 7 days at room temperature. The mean fungal growth diameter in the S. siamea treatment was 1.526 cm, slightly lower than in the C. chayamansa treatment 1.571 cm, The extracts from Cnidoscolus chayamansa and Senna siamea significantly inhibited fungal dispersion compared with the control group (p < 0.05). However, non statistically significant difference was observed between the extracts derived from the two plant specie.